Ising-type behaviour of critical properties in weak ferroelectric Li₂Ge₇O₁₅ - Kudzin, A.Yu.; Volnianskii, M.D.; Trubitsyn, M.P.; Bsoul, I.A. (Condensed Matter Physics, 1999)
The dielectric constant ε and electron spin resonance spectra of Mn²⁺
ions have been studied in the range of the ferroelectric phase transition in
Li₂Ge₇O₁₅ single crystals. Analysis of the experimental data permits one
to estimate the critical exponents of dielectric susceptibility γ ≅ 1.25, order parameter β ≅ 0.32 and correlation length ν ≅ 0.63. The values of the
critical exponents determined in a fairly broad temperature interval around
Tc, are consistent with the theoretical predictions of the Ising model with a
one-component non-polar ordering coordinate. Дiелектрична проникнiсть ε та спектри ЕПР iонiв Mn²⁺ дослiдженi в
околi сегнетоелектричного фазового переходу у кристалах
Li₂Ge₇O₁₅. Аналiз експериментальних даних дозволив оцiнити критичнi iндекси дiелектричної сприйнятливостi γ ≅ 1.25, параметра порядку β ≅ 0.32 i кореляцiйної довжини ν ≅ 0.63. Величини критичних
iндексiв, обчисленi у досить широкому iнтервалi температур поблизу Tc, узгоджуються з теоретичними показниками моделi Iзiнга для
однокомпонентного неполярного параметра порядку .